PELATIHAN PEMBUATAN SOAL LITERASI NUMERASI BERBASIS ASESMEN KOMPETENSI MINIMUM (AKM) KEPADA GURU MA AL ASYARI JOMBANG - Sholikhah, Masriatus; Ni’amah, Afi; Talen, Febyana Samara (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Community service activities were carried out at MA Al-Asy'ari with the aim of providing material and practical training on literacy development to the teaching staff. The implementation of the socialization activities was based on the challenges faced by some teachers regarding the training material they received in 2021. In general, the teachers' challenges include: 1) difficulty in understanding how to create literacy questions, and 2) confusion in developing literacy question frameworks. Based on these issues, the community service team collaborated with the madrasah to provide socialization on literacy question development, which included: 1) steps for creating literacy questions, and 2) compiling literacy question grids. The solutions to these issues will be explained in detail and implemented in three main stages: planning, implementation, and evaluation. The community service team identified several findings, including an improvement in theoretical understanding from previous activities toward practical application in developing AKM literacy questions tailored to the subject needs of the participants. During the evaluation phase, it was found that participants had gained a good understanding of literacy question development during the mentoring process for creating AKM question examples.